Rapamycin inhibits hepatitis B virus covalently closed circular DNA transcription by enhancing the ubiquitination of HBx - Zhang, Yuan; Li, Liang; Cheng, Sheng-Tao; Qin, Yi-Ping; He, Xin; Li, Fan; Wu, Dai-Qing; Ren, Fang; Yu, Hai-Bo; Liu, Jing; Chen, Juan; Ren, Ji-Hua; et al. (Frontiers in Microbiology, 2022)
Hepatitis B virus (HBV) infection is still a serious public health problem worldwide. Antiviral therapies such as interferon and nucleos(t)ide analogs effectively control HBV replication, but they cannot eradicate chronic hepatitis B (CHB) due to their inability to eliminate intracellular covalently closed circular DNA (cccDNA). Thus, there is an urgent need to develop new strategies for targeting cccDNA. As cccDNA is difficult to clear, transcriptional silencing of cccDNA is a possible curative strategy. HBx plays a vital role in maintaining the transcriptional activity of cccDNA and it could be a target for blocking the transcription of cccDNA. To screen new drugs that may contribute to antiviral therapy, the ability of 2000 small-molecule compounds to inhibit HBx was examined by the HiBiT lytic detection system. We found that the macrolide compound rapamycin, which is clinically used to prevent acute rejection after organ transplantation, could significantly reduce HBx protein expression. Mechanistic studies demonstrated that rapamycin decreased the stability of the HBx protein by promoting its degradation via the ubiquitin proteasome system. Moreover, rapamycin inhibited HBV RNA, HBV DNA and cccDNA transcription levels in HBV-infected cells. In addition, HBx deficiency abrogated the inhibition of cccDNA transcription induced by rapamycin. Similar results were also confirmed in a recombinant cccDNA mouse model. In summary, we report a new small molecule, rapamycin, which targets HBx to block HBV cccDNA transcription and inhibit HBV replication. This approach can identify new strategies to cure chronic hepatitis B.